Recent Advances in Light-Driven Carbon–Carbon Bond Formation via Carbon Dioxide Activation - Jung, Jieun; Saito, Susumu (Synthesis, 2021)
Carbon dioxide (CO2) is an attractive renewable one-carbon (C1) feedstock in terms of its earth abundance, low cost, and non-toxicity. Developing new catalytic systems to realize the practical insertion of CO2 into organic molecules has been of great importance for ecological economics. In recent years, outstanding improvements have been carried out in the field of light-driven catalytic carboxylation via the activation of CO2 as the key reagent. In this short review, the recent developments of light-promoted carboxylation utilizing CO2 to synthesize value-added chemicals using a dual visible-light photoredox/transition-metal catalyst or a photoredox catalyst are highlighted.1 Introduction2 Visible-Light-Driven Carboxylation Using Transition-Metal Photocatalysts2.1 Transition-Metal-Catalyzed Carboxylation of Alkenes2.2 Transition-Metal-Catalyzed Carboxylation of C(sp2)–X (X = Cl, Br, OTf) Bonds2.3 Transition-Metal-Catalyzed Carboxylation of Alkynes2.4 Transition-Metal-Catalyzed Carboxylation of Carbons Attached to Nitrogen3 Light-Driven Carboxylation via Organo-Photocatalysis3.1 Photocatalytic Carboxylation of Alkenes3.2 Photocatalytic Carboxylation of C(sp3)–H Bonds4 Conclusion
Keywords: carbon dioxide; photochemistry; carbon–carbon bond formation; photocatalysis; carboxylation